The composition of the global and feature specific cyanobacterial core-genomes - Simm, Stefan; Keller, Mario; Selymesi, Mario; Schleiff, Enrico (Frontiers in Microbiology, 2015)
Cyanobacteria are photosynthetic prokaryotes important for many ecosystems with a high potential for biotechnological usage e.g., in the production of bioactive molecules. Either asks for a deep understanding of the functionality of cyanobacteria and their interaction with the environment. This in part can be inferred from the analysis of their genomes or proteomes. Today, many cyanobacterial genomes have been sequenced and annotated. This information can be used to identify biological pathways present in all cyanobacteria as proteins involved in such processes are encoded by a so called core-genome. However, beside identification of fundamental processes, genes specific for certain cyanobacterial features can be identified by a holistic genome analysis as well. We identified 559 genes that define the core-genome of 58 analyzed cyanobacteria, as well as three genes likely to be signature genes for thermophilic and 57 genes likely to be signature genes for heterocyst-forming cyanobacteria. To get insights into cyanobacterial systems for the interaction with the environment we also inspected the diversity of the outer membrane proteome with focus on β-barrel proteins. We observed that most of the transporting outer membrane β-barrel proteins are not globally conserved in the cyanobacterial phylum. In turn, the occurrence of β-barrel proteins shows high strain specificity. The core set of outer membrane proteins globally conserved in cyanobacteria comprises three proteins only, namely the outer membrane β-barrel assembly protein Omp85, the lipid A transfer protein LptD, and an OprB-type porin. Thus, we conclude that cyanobacteria have developed individual strategies for the interaction with the environment, while other intracellular processes like the regulation of the protein homeostasis are globally conserved.